Given f(x)=x^2, write the equation of the transformed function if g(x)=f(x-1)
![Given fxx2 write the equation of the transformed function if gxfx1 class=](https://us-static.z-dn.net/files/db0/c00b9a2e7a47a0e6e47510d27e555656.jpg)
Answer:
1. g(x) = (x - 1)²; translation of 1 unit to the right.
2. g(x) = 3^(x + 1) - 2; translation to the left of 1 unit and translation of 2 units down.
Step-by-step explanation:
1.
f(x) = x²
g(x) = f(x - 1)
g(x) = (x - 1)²
Since x was replaced by x - 1, g(x) is similar to f(x) with a translation of 1 unit to the right.
2.
f(x) = 3^x
g(x) = f(x + 1) - 2
g(x) = 3^(x + 1) - 2
Since x was replaced by x + 1, which is the same as x - (-1), there is a translation to the left of 1 unit. In addition, the -2 causes a translation of 2 units down.